An Examination of Disgust and Its Relation to Morality - Wood, Jessa (Stance: an international undergraduate philosophy journal, 2014)
In his book Yuck!: The Nature and Moral Significance of Disgust, Daniel Kelly synthesizes a growing body of research on disgust and briefly explores the philosophical role of the emotion. This paper presents arguments for the position that disgust should not be considered a source of moral knowledge, a position that Kelly suggests but fails to illustrate. The paper also explores implications of this view, specifically concerning the ways we should seek to manipulate our disgust reactions in order to improve moral reasoning.